An efficient heat transfer analysis of MHD flow of hybrid nanofluid between two vertically rotating plates using Keller box scheme - Mohib Hussain; Muhammad Imran; Hassan Waqas; Taseer Muhammad; Sayed M. Eldin (Case Studies in Thermal Engineering, 2023)
Nowadays, the majority of pharmaceuticals are created as hybrid nanofluids, and blood is used as a base fluid for testing to determine how the various components of the blood interact chemically. The thermal efficiency of the base liquids is also improved by the hybrid nanofluids. Moreover, the impacts of thermal radiation are also considered. Blood is used as base fluid. To investigate the characteristics of phenomena, we research two different forms of fluid flow, one of which is a hybrid nanofluid and the other of which is a nanofluid flow. The governing set of PDEs is transformed into a set of ODEs with the help of suitable similarity transformations. Nonlinear ODEs are numerically solved with the help of well reputed Keller box technique. Graphical and numerical results versus different physical and engineering parameters are computed by the computational software Matlab. The temperature profile is improved by increasing values of the heat source-sink parameter because the parameter causes the fluid to produce more heat. The volume fraction parameter reduces the fluid's velocity. The velocity profile measured against the suction parameter shows the same form. This study may control various aspects of the microcirculatory system, including the drug delivery process.